An Advisor like Me: Does Gender Matter? - Takao Kato; Yang Song (Institute of Labor Economics (IZA), 2018)
This paper provides new causal evidence on the effects of gender congruence in the student-adviser relationship on three key student outcomes: (i) retention; (ii) grades; and (iii) post-graduation career outcomes. In so doing, we use unique administrative data from a selective liberal arts university which includes detailed longitudinal records on all students. Our identification strategy is based on the University's first-year faculty adviser assignment policy which produces randomness in whether a student has a same-gender faculty adviser. First, we find that gender congruence in the student-adviser relationship has a positive and significant effect on the odds of retention (gender congruence effect on the extensive margin) and on cumulate GPA upon graduation (gender congruence effect on the intensive margin). Second, we uncover that much of the gender congruence effect on the extensive margin tends to be concentrated in the freshman and sophomore years, while the gender congruence effect on the intensive margin is less immediate and shows up only in cumulative GPA upon graduation. The results are found to change little when we account for unobserved adviser characteristics by using adviser fixed effects. Finally, student-adviser gender congruence is found to work differently for students with different backgrounds and interests. Most notably we find that gender congruence in the student-adviser relationship is particularly helpful for academically weak students and students without STEM-orientation.
Keywords: I21; I23; 330; higher education; gender congruence; advising; academic outcomes; labor market outcomes